Control of Neobenedenia sp. Infestations in the Ocean Tank at Gran Acuario Mazatlán - Francisco Neptalí Morales-Serna; Dania López-Moreno; José Antonio Velázquez Garay; Luis Antonio Rendón-Martínez (Parasitologia, 2025)
The Gran Acuario Mazatlán (GAM), Mexico’s largest aquarium, is located at the entrance of the Gulf of California. In April 2023, fish in the Ocean Tank (OT) began exhibiting disease symptoms, followed by significant mortality, primarily affecting Caranx caninus, Chaetodipterus zonatus, and Lutjanus colorado. Parasitological examinations identified heavy infestations of Neobenedenia sp. (Monogenea: Capsalidae), with parasites extensively covering body surfaces and gills of some individuals. To control the outbreak, an environmental management strategy was implemented, involving a gradual reduction in water temperature (from 26 °C to 22 °C) and salinity (from 35 ppt to 26 ppt), increased cleaning frequency, and parasite egg abundance monitoring. Over time, egg abundance declined, and by July, fish behavior and feeding rates had returned to normal, with parasite-associated mortality dropping below 2%. Preventive measures, including strict quarantine protocols for new fish, have been implemented to maintain optimal conditions in the OT. This case highlights the challenges of managing parasite outbreaks in large, multi-species aquaria and underscores the importance of environmental control strategies in marine animal care.